2004
DOI: 10.2355/isijinternational.44.1615
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Manganese Ores by Methane-containing Gas

Abstract: Reduction of Groote Eylandt (Australia) and Wessels (South Africa) manganese ores using CH 4 -H 2 -Ar gas mixture was investigated in a fixed bed laboratory reactor in the temperature range 1 000-1 200°C. The extent and kinetics of manganese ore reduction as a function of gas composition and temperature were determined by on-line off-gas analysis using mass-spectrometer and dew point sensor. Morphology of ores and its change in the course of reduction was examined by optical and scanning electron microscopy. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Formation of a liquid phase in the process of reduction of Groote Eylandt ores was a significant factor affecting the ore reduction. In reduction of GE-PF ore by methane containing gas studied by Anacleto et al, 20) extent and rate of reduction significantly decreased with increasing temperature from 1 100°C to 1 200°C; degree of reduction of this ore at 1 200°C was slightly above 50 % after 5 h of reaction. This was attributed to the formation of a liquid phase and decrease in the interfacial reaction area with blockage of methane-hydrogen gas access to the ore interior.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Formation of a liquid phase in the process of reduction of Groote Eylandt ores was a significant factor affecting the ore reduction. In reduction of GE-PF ore by methane containing gas studied by Anacleto et al, 20) extent and rate of reduction significantly decreased with increasing temperature from 1 100°C to 1 200°C; degree of reduction of this ore at 1 200°C was slightly above 50 % after 5 h of reaction. This was attributed to the formation of a liquid phase and decrease in the interfacial reaction area with blockage of methane-hydrogen gas access to the ore interior.…”
Section: Discussionmentioning
confidence: 85%
“…Doping of the GE-PF ore with lime (10-15 % CaO) increased the ore melting temperature and significantly enhanced reduction rate and extent at 1 200°C. 20) Carbothermal reduction behaviour of GE ores was very different from that observed in reduction by methane-containing gas. The major difference between these processes is obvious: carbon is intimately mixed with oxides in the carbothermal reduction, while in reduction by CH 4 -H 2 gas, carbon is delivered to the ore interior from the gas phase.…”
Section: Discussionmentioning
confidence: 92%
“…As discussed before, the higher that ratio, the more active is the catalyst because more oxygen is exposed on the catalyst surface to be converted. which coexist on the catalyst surface [121]. We also found that the total amount of stored oxygen, which has to be released for reduction of Mn 2 O 3 into MnO, was never reached.…”
Section: Variation Of the Support Materialsmentioning
confidence: 76%
“…However, the findings of Jones et al indicate that also the manganese oxide is able to form active sites for the selective activation of methane [122]. As reported by other groups, supported manganese oxides tend to form also deep oxidation products [121,123,112], Therefore, the proposed redox mechanism of Jiang et al has to be extended according to equations (43)- (45), which considers further redox activity of manganese oxide, as the total oxidation reaction of methane and also a selective activation. However, due to the fact that even small amounts of Na 2 WO 4 enhances the methane conversion and the C 2 selectivity, the reaction rates of equations (38) - (42) must be higher compared to the reaction rates in equations (44)- (45).…”
Section: )mentioning
confidence: 84%
See 1 more Smart Citation